Tennessee Information Retrieval and Dissemination System for Vocational Education. Final Report (July 1, 1970-June 30, 1971) - Tennessee Univ., Knoxville. Occupational Research and Development Coordinating Unit.; Wilder, Dolores J.; Tennessee Univ., Knoxville. Occupational Research and Development Coordinating Unit.; Tennessee Univ., Knoxville ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
In order to move information concerning vocational and technical education from the library into the hands of practitioners, the Tennessee Research Coordinating Unit (RCU) in cooperation with the State Division of Vocational-Technical Education decided to develop a system of information retrieval and dissemination. Such a system has been developed through a series of seven phases which are: (1) minor remodeling of RCU facility to accommodate research library and resource materials, (2) installation of ERIC tapes on computer system, (3) development of a cataloging and filing system for materials, (4) installation of microfiche readers and files in 13 locations throughout the state, (5) updating of microfiche and related files, (6) workshops to orient users on availability and use of materials and equipment, and (7) development of a selective dissemination of information system for user groups. This report discusses each of these phases of development. Supplementary data in the appendix include a computer search questionnaire which was used to collect feedback on computer searches performed by the Tennessee RCU. (JS)
Availability: Tennessee Research Coordinating Unit for Vocational Education, 909 Mountcastle Street, Knoxville, Tennessee 37916.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computer Assisted Instruction; Educational Facilities; Educational Researchers; Information Retrieval; Information Systems; Information Utilization; Laboratories; Microfiche; Research Coordinating Units; Research Libraries; Research Tools; Research Utilization; Vocational Education; ERIC -- Tennessee